New education of Bologna: transformed classroom by Techno-holistic paradigm - Melgarejo Moreno, Irene; Rodríguez Rosell, María del Mar (Historia y Comunicación Social, 2014)
New communication processes transform teacher’s role that becomes a guide in the process of teaching/learning. This new challenge causes two consequences: the need for a methodology to meet new cultures of communication and transformation in design of the new university classroom. This article includes a proposal for a practical example of agora adapted to the new demands for society which shows the possibilities for good use of the media applied to teaching.
Keywords: communication; teaching; media; classroom and education.